2015
DOI: 10.1590/01000683rbcs20150121
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Sorghum Performance Affected by Soil Compaction and Sowing Time as a Second Crop in the Brazilian Cerrado

Abstract: Increasing attention has recently been given to sweet sorghum as a renewable raw material for ethanol production, mainly because its cultivation can be fully mechanized. However, the intensive use of agricultural machinery causes soil structural degradation, especially when performed under inadequate conditions of soil moisture. The aims of this study were to evaluate the physical quality of aLatossolo Vermelho Distroférrico (Oxisol) under compaction and its components on sweet sorghum yield forsecond cropsowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Todavia, a maior valor de ºBrix deve estar associado à produtividade de colmos e caldo que resultará em maior produtividade de etanol. Guimarães Júnnyor et al (2015) verificaram redução na produção de colmo e no valor de ºBrix em semeadura tardia, ocasionado pelas condições climáticas, devido a deficiência hídrica.…”
Section: Resultsunclassified
“…Todavia, a maior valor de ºBrix deve estar associado à produtividade de colmos e caldo que resultará em maior produtividade de etanol. Guimarães Júnnyor et al (2015) verificaram redução na produção de colmo e no valor de ºBrix em semeadura tardia, ocasionado pelas condições climáticas, devido a deficiência hídrica.…”
Section: Resultsunclassified
“…To set up the experiment, the following activities were initially carried out: two subsoiling operations crossed at a depth of 0.40 m, one plowing and two harrowing operations, with the aim of eliminating the historical tension in the area. Subsequently, the soil was compacted using an agricultural tractor with a tare weight of 4.5 Mg when the soil was close to field capacity and passed four times in the same place throughout the area, following the procedure described by Guimarães Júnnyor et al [64]. O.M.…”
Section: Study Site and Experimental Arrangementmentioning
confidence: 99%
“…Intermediary values needed to estimate LLWR were(i) soil moisture at field capacity (θ FC ), (ii) soil moisture at permanent wilting point (θ PWP ), (iii) soil moisture at 0.10 m 3 m -3 air-filled porosity (θ AP ) was, and (iv) soil moisture at 2.5 MPa soil penetration resistance (θ PR ) as proposed by Severiano et al (2011), Gonçalves et al (2014), Guimarães Júnnyor et al (2015).…”
Section: Parameters Measuredmentioning
confidence: 99%
“…Values of Bd c higher than these probably present limiting conditions to plant development despite the water content in the soil due to structural restrictions. Guimarães Júnnyor et al (2015) evaluated physical quality of a oxisol (clay 44%) and found Bd c of 1.36 Mg m -3 . According to Petean et al (2010), low Bd c increases the possibility of Bd achieving critical values (Bd > Bd c ), suggesting a higher incidence of limiting physical conditions for plant development.…”
Section: Least Lmentioning
confidence: 99%
See 1 more Smart Citation